The Learner Support Programs: How Do They Work for Increasing Students’ Retention? - Hidayah, Hidayah; Hadianti, Siti; Ayuni, Devi (Smart Education, 2024)
Abstract: Universitas Terbuka (UT) in Indonesia is a pioneer in distance learning that offers comprehensive learning support programs to improve student retention. Assignment workshops and exam clinics provide valuable guidance and support to help students overcome academic challenges and achieve their educational goals. Continued investment in these support services is essential for promoting student retention and fostering a positive learning environment. This paper discusses how learner support programs implemented by Universitas Terbuka enhance student retention. These programs include distance learning skill workshops, assignment workshops, and exam clinics, which provide academic assistance and guidance to support students’ independent study. This study employs a qualitative research method involving questionnaires and in-depth interviews. The participants were students from the Bachelor of English Education Study Program. The results indicate that learner support programs positively impact student academic success and retention by increasing students' confidence, enhancing their technology literacy skills, and fostering their independence. It can be concluded that learner support programs employed by UT are strategically important for maintaining student satisfaction, supporting student success, and improving retention rates.Keywords: assignment workshops; exam clinics; Universitas Terbuka; distance learning; student retention